IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA BANK BENGKULU - Ahmad Sumarlan; Budi Astuti; Nensi Yuniarti. Zs (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2021)
The importance of this CSR (Corporate Social Responsibility) program has become a global trend with the increasing concern for prioritizing stakeholders. With the advancement of information technology and market openness, companies must seriously and openly pay attention to CSR. Law No. 40/2007 concerning Limited Liability Companies requires the implementation of social and environmental responsibilities. The law also requires all companies to report the implementation of these responsibilities in the Annual Financial Performance Report.               This study uses a qualitative approach. Hariwijaya (2007:43) defines qualitative research as research that does not use mathematical, statistical or computer models. The research process begins with developing the basic assumptions and rules of thought that will be used in the research. The assumptions and rules of thinking are then applied systematically in data collection and processing to provide explanations and arguments. In qualitative research, the information collected and processed must remain objective and not influenced by the opinion of the researcher himself.This study uses a qualitative approach, qualitative research is research that intends to understand the phenomena of what is experienced by the research subject, for example behavior, perception, motivation, action, holistically, and by way of description in the form of words and language, in a special context. natural and by utilizing various scientific methods According to Moleong (2005:6).               It was concluded that the implementation of the CSR (Corporate Social Responsibility) program at Bank Bengkulu was concluded as follows;a. Implementation of CSR (Corporate Social Responsibility) carried out by PT. Bank Bengkulu is to realize CSR funds that are distributed annually at least 70% of the CSR fund budget that has been determined, then the funds are realized to the community or public interest which is the target of Bank Bengkulu based on CSR principles. The funds are channeled through activities that have been planned based on the scope or field of CSR for one year.b. The forms of CSR implementation at Bank Bengkulu in the social sector that have been carried out by PT. Bank Bengkulu such as providing scholarships to outstanding students, providing book assistance, social welfare, caring for natural disasters and others. In the field of economics PT. Bank Bengkulu implements CSR activities such as SMEs, providing tax cars for Bengkulu province, opening employment opportunities, and other productive businesses. while in the field of environmental CSR which has been carried out by PT. Bank Bengkulu such as maintaining the cleanliness of the environment around the office, reforestation, nature conservation such as planting a thousand trees, environmental sanitation and others. CSR Keywords